1999
DOI: 10.1006/viro.1999.9834
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons and IRF-1 Play a Critical Role in the Control of a Gammaherpesvirus Infection

Abstract: The murine gammaherpesvirus 68 (MHV-68) is an ideal model system for the study of interactions between gammaherpesviruses and their hosts. Intranasal infection of mice with MHV-68 results in replication of the virus in the lung epithelium followed by latent infection of B cells. Resolution of productive MHV-68 infection depends on the adaptive immune system, but little is known about the role of innate immune mechanisms and the early interaction between the host and the virus. In this report, we have used mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 30 publications
8
82
1
Order By: Relevance
“…Alternatively, an increased activity of CD4 ϩ CD25 ϩ T regulatory cells following infection might have also suggested that such a host response was necessary to limit viral-induced pathophysiology. This too would have been consistent with our understanding of ␥HV-68 pathology, which routinely resolves itself in normal mice, but can be greatly exacerbated in mice which have immune defects (45,46). Surprisingly, we found that the levels of FoxP3 mRNA ( Figs.…”
Section: Discussionsupporting
confidence: 69%
“…Alternatively, an increased activity of CD4 ϩ CD25 ϩ T regulatory cells following infection might have also suggested that such a host response was necessary to limit viral-induced pathophysiology. This too would have been consistent with our understanding of ␥HV-68 pathology, which routinely resolves itself in normal mice, but can be greatly exacerbated in mice which have immune defects (45,46). Surprisingly, we found that the levels of FoxP3 mRNA ( Figs.…”
Section: Discussionsupporting
confidence: 69%
“…For example, ifnar −/− mice are very sensitive to VSV infection, whereas ifngr −/− mice are resistant (1). Immune-mediated inhibition of acute MHV-68 infection also requires type I but not type II IFNs (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Early IFN-␣/␤ production is critical for controlling acute viral infection (18), and it has been suggested that early chemokine production might also contribute to the protective host response. Such a suggestion is supported by the observation that the viral M3 gene encodes a soluble chemokine receptor (19,20) that can compete for chemokine binding (19).…”
Section: Urine ␥-Herpesvirus-68 (␥Hv-68)mentioning
confidence: 99%